Motor abilities of the hand in judo and kick-boxing athletes - Karaleic, S.; Puzovic, V.; Milenkovic, V.; Savic, Z.; Andjelkovic, I. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Motor abilities of the hand are considered as important factor for successful task performing in combat sports. The aim of this study was to evaluate differences in hand motor abilities of athletes from two combat sports with different style of fighting, judo and kick-boxing. Subjects and methods: This study included 36 male athletes, age 16-17 years old. They were divided in two groups per 18 athletes, by the sport they train, judo and kick-boxing group. All the athletes compete in the first league for their age category. Criteria for including in the study was that they train their sport at least 4 years, and that height of the athlete is between 178-184 cm, and weight between 65-72 kg. Under motor abilities of the hand we tested grip force, pinch force and hand and fingers coordination. Grip and pinch force were evaluated with Lafayette hydraulic dynamometers, while hand and fingers coordination were evaluated with Minnesota rate of manipulation test and Nine-hole peg test. All tests were done with dominant hand. Statistical procedures were done with statistical package PASW 18. Results: Judo athletes had a significantly higher grip (46.8 ± 6.2 kg) and pinch force (7.7 ± 0.9 kg) in comparing with results from kick-boxing athletes, 38.4 ± 5.4 kg and 6.1 ± 1.1 kg for grip and pinch force respectively, with p = 0.001 for both tests. In Minnesota rate of manipulation test, which we used to evaluate speed and coordination of the arm, hand and fingers, kick-boxing athletes had significantly better results in comparing with judo athletes, with p = 0.001. However, in Nine-hole peg test for evaluation of fingers and hand coordination judo athletes had better results but without statistical significance, p = 0.078. Conclusion: In conclusion we can say that majority of results from this study goes along with specific sports requirements for these two combat sports. However, we expected better pinch and grip force results from kick-boxing athletes, because weak hand muscle in this sport may lead to the injury.